Characterization of Salinivibrio socompensis sp. nov., A new halophilic bacterium isolated from the high-altitude hypersaline lake Socompa, Argentina - Galisteo, Cristina (2019)
The genus Salinivibrio belongs to the family Vibrionaceae and includes Gram-stain-negative, motile by a polar flagellum, and facultatively anaerobic curved rods. They are halophilic bacteria commonly found in hypersaline aquatic habitats and salted foods. This genus includes five species and two subspecies. A presumed novel species, strain S35T, was previously isolated from the high-altitude volcanic, alkaline, and saline lake Socompa (Argentinean Andes). In this study we carried out a complete taxonomic characterization of strain S35T, including the 16S rRNA gene sequence and core-genome analysis, the average nucleotide identity (ANIb, ANIm, and orthoANI), and in silico DNA?DNA hybridization (GGDC), as well as the phenotypic and chemotaxonomic characterization. It grew at 3%?20% (w/v) NaCl, pH 6?10, and 10?42 °C, with optimum growth at 7.0%?7.5% (w/v) NaCl, pH 8.0, and 37 °C, respectively. Strain S35T was oxidase- and catalase-positive, able to produce acid from D-glucose and other carbohydrates. Hydrolysis of DNA, methyl red test, and nitrate and nitrite reduction were positive. Its main fatty acids were C16:0, C16:1 ω7c and C16:1 ω6c, and C18:1 ω7c and/or C18:1 ω6c. ANI, GGDC, and core-genome analysis determined that strain S35T constitutes a novel species of the genus Salinivibrio, for which the name Salinivibrio socompensis sp. nov. is proposed. The type strain is S35T (= CECT 9634T = BNM 0535T)